Mechanism of action of Cry1ac toxin from Bacillus thuringiensis in Helicoverpa armigera (Lepidoptera: Noctuidae) - Silva, Igor Henrique Sena da [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
- Helicoverpa armigera (Hübner, 1805) (Lepidoptera: Noctuidae), known as Cotton bollworm is an insect pest of global importance in cotton crop. Nonetheless, it also attacks several other important economic crops worldwide, such as soybeans, corn, sorghum, wheat, beans, tomatoes, and ornamental plants. This insect is susceptible to some insecticidal Cry toxins from Bacillus thuringiensis (Bt) expressed in transgenic plants (Bt plants) or used in biopesticides. However, the capacity to evolve resistance to Bt plants have been threaten the technology in the long term. The most common mechanisms of resistance of lepidopterans to Cry toxins are mutations linked to Cry toxins receptors resulting in reduced binding. Thus, the identification and characterization of the putative Cry receptors is fundamental to better understand the mode of action of Cry toxins, retarding resistance evolution and producing Cry toxins more effective against insect pests. Previously, we identified H. armigera prohibitin (PHB) as a Cry1Ac-binding protein. The aim of this work was to further analyzed the potential role of PHB as a Cry toxin receptor in comparison to cadherin (CAD), a midgut protein (MP) well-recognized as Cry1Ac-receptor. In addition, to characterize the interaction of those two MP with different Cry1A toxins. In this way, HaPHB-2 midgut protein and HaCAD toxin binding region fragment (TBR) from H. armigera were expressed in Escherichia coli cells and qualitative and quantitative binding assays with different Cry1 toxins were performed, as well as competition assays. We demonstrated that Cry1Ab, Cry1Ac and Cry1Fa toxins bound to HaPHB-2 similarly as to HaCAD-TBR. HaPHB-2 protein competed with Cry1Ac binding to H. armigera BBMVs. A reduction of toxin binding to HaBBMV was observed in the presence of HaPHB-2 in a concentration dependent way. Furthermore, different Cry1Ab mutant toxins located in domain II (Cry1Ab-F371A and Cry1Ab-G439D) or domain III (Cry1Ab-L511A and Cry1Ab-N514A), that were previously characterized to be affected in receptor binding, were analyzed regarding to their binding interaction with HaPHB-2 and toxicity against H. armigera. One β-16 mutant (Cry1Ab-N514A) showed increased binding to HaPHB-2 that correlated with six-fold higher toxicity against H. armigera while the other β-16 mutant (Cry1Ab-L511A) that was affected in binding to HaPHB-2 lost toxicity against H. armigera. We have found that the β-16 region from domain III of Cry1Ab is involved in interaction with HaPHB-2 and toxicity. This work identified a region of Cry1Ab involved in binding to HaPHB-2 from a Lepidoptera insect suggesting that this midgut protein may participate as a novel receptor in the mechanism of action of the Cry1 toxins in H. armigera. This is the first characterization of HaPHB-Cry1A interaction, supporting that HaPHB-2 also participates in the mechanism of action of Cry1Ab toxin in H. armigera, presenting new insights of the mode of action of Cry1 toxins in this important global pest.

Helicoverpa armigera (Hübner, 1805) (Lepidoptera: Noctuidae), conhecida como lagarta Helicoverpa é uma praga de importância global na cultura do algodão. No entanto, também ataca várias outras culturas de importância agrícola em todo o mundo, como soja, milho, sorgo, trigo, feijão, tomate e plantas ornamentais. Este inseto é suscetível a algumas toxinas inseticidas Cry de Bacillus thuringiensis (Bt) expressas em plantas transgênicas (plantas Bt) ou usadas em bioinseticidas. No entanto, a capacidade de desenvolver resistência às plantas Bt tem ameaçado a tecnologia a longo prazo. Os mecanismos mais comuns de resistência dos lepidópteros às toxinas Cry são mutações ligadas aos receptores das toxinas, resultando na redução da ligação. Assim, a identificação e caracterização dos receptores Cry é fundamental para melhor compreender o modo de ação das toxinas e retardar a evolução da resistência e assim produzir novas toxinas Cry mais eficazes contra os insetos-praga. Previamente, nós identificamos a proibitina (PHB) de H. armígera como uma proteína de ligação a Cry1Ac. O objetivo deste trabalho foi analisar a potencial função de PHB como receptor da toxina Cry em comparação com a caderina (CAD), uma proteína do intestino médio bem conhecida como receptor de Cry1Ac. Além disso, caracterizar a interação dessas duas proteínas de membrana à diferentes toxinas Cry1A. Desta forma, a proteína HaPHB-2 e um fragmento da região de ligação da toxina a HaCAD de H. armigera foram expressos em células de Escherichia coli e ensaios de ligação qualitativos e quantitativos com diferentes toxinas Cry1 foram realizados, bem como ensaios de competição. Nós demonstramos que as toxinas Cry1Ab, Cry1Ac e Cry1Fa se ligaram ao HaPHB-2 de forma semelhante a HaCAD. A proteína HaPHB-2 competiu com a ligação de Cry1Ac as BBMVs de H. armigera. Uma redução da ligação da toxina às HaBBMVs foi observada na presença de HaPHB-2 em uma forma dependente da concentração. Além disso, diferentes toxinas mutantes de Cry1Ab localizadas no domínio II (Cry1Ab-F371A e Cry1Ab-G439D) ou domínio III (Cry1Ab-L511A e Cry1Ab-N514A), que haviam sido previamente caracterizadas como afetadas na ligação ao receptor, foram analisadas em relação à sua interação de ligação com HaPHB-2 e toxicidade contra H. armigera. Uma toxina mutante em β-16 (Cry1Ab-N514A) mostrou ligação aumentada a HaPHB-2, o que correlacionou com toxicidade seis vezes maior contra H. armigera, enquanto outro mutante de β-16 (Cry1Ab-L511A) que foi afetado na ligação a HaPHB-2 perdeu toxicidade contra H. armigera. Nós encontramos que a região β-16 do domínio III de Cry1Ab está envolvida na interação com HaPHB-2 e toxicidade. Este trabalho identifica a região de Cry1Ab envolvida na ligação ao HaPHB-2 de um inseto da ordem Lepidoptera, sugerindo que esta proteína de membrana pode participar como um novo receptor no mecanismo de ação das toxinas Cry1 em H. armigera. Esta é a primeira caracterização da interação HaPHB-Cry1A, corroborando que HaPHB-2 também participa do mecanismo de ação da toxina Cry1Ab em H. armigera, aumentando a compreensão sobre o modo de ação das toxinas Cry1 nesta importante praga global.
Mecanismo de ação da toxina Cry1ac de Bacillus thuringiensis em Helicoverpa armigera (Lepidoptera: Noctuidae)
Keywords: Lagarta Helicoverpa; Toxinas Cry; Mecanismo de ação; Manejo de resistência de insetos; Bacillus thuringiensis; Cotton bollworm; Cry toxins; Mechanism of action; Resistance management; Cadherin; Prohibitin